Antibacterial Activity of Defatted and Nondefatted Methanolic Extracts of Aframomum melegueta K. Schum. against Multidrug-Resistant Bacteria of Clinical Importance - Olufunmiso Olusola Olajuyigbe; Otunola Adedayo; Roger Murugas Coopoosamy (The Scientific World Journal)
The antibacterial activity of the extracts of Aframomum melegueta including n-hexane extract (NHE), nondefatted methanol extract (NDME), and defatted methanol extract (DME) was investigated in this study. The NHE exhibited no antibacterial activity. The DME showed higher antibacterial activity than the NDME against the different isolates. At the highest concentration of 10 mg/mL in agar diffusion, NDME produced inhibition zones ranging from 11 to 29 mm against the microorganisms while DME produced inhibition zones ranging from 20 to 40 mm with the concentration of 10 mg/mL against the microorganisms. 0.1 mg/mL of the DME produced inhibition zones ranging between 12 and 14 mm in Aeromonas hydrophila ATCC 35654 and Pseudomonas aeruginosa ATCC 15442, respectively, while none of the isolates were inhibited by the NDME at a concentration of 1 mg/mL or less. In the agar dilution assay, the MICs of the NDME and DME ranged between 0.31 and 10 mg/mL, but more isolates were inhibited at 0.31 mg/mL of DME than those in NDME. In macrobroth assay, the MICs of the NDME ranged between 0.15 and 5.0 mg/mL and the MBCs ranged between 0.63 and 5.0 mg/mL, and the MICs of the DME ranged between 0.08 and 5.0 mg/mL and the MBCs were between 0.31 and 5.0 mg/mL. This study indicated that DME was more active with higher antibacterial activity than the NDME of this plant, and extracting the fatty portion of plant materials prior susceptibility testing would allow plant extracts to be more effective as well as justifying the use of Aframomum melegueta in traditional medicine for the treatment of bacterial infections.